After Suez adrift in the American century - Woollacott, Martin (I.B. Tauris, 2006)
With Tony Blair and George Bush's authority ever more threatened by the blowback from their venture in the Middle East, the Suez Crisis of 1956, has taken on a new relevance. Years after Antony Eden's fateful decision to take on the Egyptian President, this work retraces the legacy of this dramatic foreign policy blunder.